Dysfunctional Family Environment Explaining Direct and Indirect Aggression in Adolescents - Rodríguez-Naranjo, María Carmen; Caño-González, Antonio (My University, 2014)
The aim of this study was to examine the relationship between family functioning (problem solving, communication, roles, affective responsiveness, affective involvement, behaviour control and general functioning) and the development of different expressions of aggressive behaviour in adolescents. Data were collected from a sample of 722 Spanish adolescents who completed the Family Assessment Device and the self-report form of the Children’s Social Behavior Scale. Regression analyses confirmed the specific influence of different dimensions of family functioning on specific types of aggressive behaviour in adolescents when controlling (i) the other type of direct or indirect aggressive behaviours; ii) the overlapping effects of family functioning dimensions on each type of aggression. The results showed two dimensions on its own, communication and roles, predicting specifically direct aggression, whereas all the family dimensions as a whole predicting specifically indirect aggression. These findings pointed out that a better understanding of family functioning dimensions is necessary in order to design specific interventions for aggressive adolescents.
Keywords: Niños - Malos tratos; Family environment; Aggression; Adolescence